The author’s responsibility. The Essay Mädchen by Theresa Präauer - Vicheva, Violeta (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
This text examines Teresa Präauer’s essay as an opportunity to approach the answer to the questions of engagement in art today, of the elusive boundary between radical and provocative art on the one hand and tendentious provocation on the other. By examining the way in which the essay names the definitions and limitations related to the girl, the article traces the relationship between the writer’s stated method and its application. The established inconsistency is interpreted as provoking the need for reader engagement at the expense of the author’s and in relation to the topic.